Do Muslim Women Need Saving? - Lila Abu-Lughod (Harvard University Press, 2013)
This book seeks answers to the questions that presented themselves to me with such force after September 11, 2001, when pop u lar concern about Muslim womenâ€™s rights took off. I worry about the ways that repre sen ta tions of Muslim womenâ€™s suffering and arguments about their lack of rights have been working politi cally and practically. I follow the concept of â€œMuslim womenâ€™s rightsâ€ as it travels through debates and documents, organizes womenâ€™s organizations and activism, and mediates lives in refugee camps and the halls of the United Nations. I try to uncover what this framework that describes distant womenâ€™s lives only in terms of rights, present or absent, hides from us about both everyday violence and forms of love. I ask what evaluating lives in terms of rights does for (and against) different kinds of women. Along the way, I uncover how key symbols of Muslim womenâ€™s cultural aliennessâ€” from the veil to the honor crimeâ€” are deployed in twenty- fi rst- century po liti cal projects, and why these symbols grip us. Trying to understand peopleâ€™s lives is for me a passion. It is also my vocation as an anthropologist. That is why I seek answers to these big questions through the lives of par tic u lar women I know. These are women who are trying to lead good lives and who are making choices that are sometimes hard, limited by the constraints of the present and the uncertainties of the future. I have known them for many years, as individuals living in families, communities, countries, and the world. How do they see the problems they are facing? What do they say they want? How should this make us think about that mythical place where Muslim women, undifferentiated by nation, locality, or personal circumstance, live lives that are totally separate and different from our own? What can thinking about their circumstances teach us about values like choice and freedom in the context of human livesâ€” any human lives?